Lithium increases slow wave sleep: possible mediation by brain 5-HT2 receptors? - Friston, K; Sharpley, A; Solomon, R; Cowen, P (Springer-Verlag, 1989)
The effect of lithium on slow wave sleep (SWS) was studied in ten normal male volunteers using home based cassette sleep recording and automatic sleep stage analysis. Lithium increased SWS, an effect consistent with a reduction in brain 5-HT2 receptor function.